2020
DOI: 10.1111/clr.13636
|View full text |Cite
|
Sign up to set email alerts
|

An advanced prediction model for postoperative complications and early implant failure

Abstract: Objectives: Risk prediction in implant dentistry presents specific challenges including the dependence of observations from patients with multiple implants and rare outcome events. The aim of this study was to use advanced statistical methods based on penalized regression to assess risk factors in implant dentistry. Material and methods: We conducted a retrospective study from January 2016 to November 2018 recording postoperative complications including bleeding, hematoma, local infection, and nerve damage, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
8
1
1
Order By: Relevance
“…Beyond the effect of SST, we observed in our study that implant placement with sedation (3.4‐fold), simultaneous bone grafting (3.7‐fold), simultaneous soft tissue grafting (5‐fold), occurrence of intra‐operative complications (6‐fold), pre‐placement ridge augmentation (7.5‐fold), and number of implants (1.2‐fold) increase the risk for EIF. The finding that EIF was significantly higher in sites with pre‐placement ridge augmentation contradicts two earlier retrospective studies that reported no association between bone augmentation (guided bone regeneration or sinus floor elevation) and early or late implant loss (Feher et al., 2020; Tran et al., 2016). However, in another study, less marginal bone loss was associated with implants placed in native compared with augmented bone (Thoma et al., 2019).…”
Section: Discussioncontrasting
confidence: 60%
“…Beyond the effect of SST, we observed in our study that implant placement with sedation (3.4‐fold), simultaneous bone grafting (3.7‐fold), simultaneous soft tissue grafting (5‐fold), occurrence of intra‐operative complications (6‐fold), pre‐placement ridge augmentation (7.5‐fold), and number of implants (1.2‐fold) increase the risk for EIF. The finding that EIF was significantly higher in sites with pre‐placement ridge augmentation contradicts two earlier retrospective studies that reported no association between bone augmentation (guided bone regeneration or sinus floor elevation) and early or late implant loss (Feher et al., 2020; Tran et al., 2016). However, in another study, less marginal bone loss was associated with implants placed in native compared with augmented bone (Thoma et al., 2019).…”
Section: Discussioncontrasting
confidence: 60%
“…The evolution of the techniques and materials adopted has allowed more doctors and patients to use this type of therapy, making possible the placement of implant elements in very hard situations where only a few years ago the professional would have chosen a different therapeutic choice [ 36 ]. One of the main principles for successful therapy is the achievement of suitable primary stability during the implant placement [ 37 ] in respect to the biology of the host [ 38 ] and factors depending on the invasiveness of the operation; the more the preparation of the implant site will be performed in an atraumatic way by avoiding the overheating, and so the necrosis of the site, the more we will be able to respect tissues of the host by avoiding intra- and post-operation complications (bleeding, swelling, local infection, invasion of the noble structures adjacent to the surgery, implant early loss, inadequate healing of hard and soft tissues involved during the operation, presence and/or formation of pus immediately after the operation, pain, alteration of the sensitivity of the area) [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the surgery, we may assess the primary stability of the placed implants, a value that indicates the contact of the implant surface with the surrounding bone [ 42 ]; after this, the secondary stability will follow, which is reached after the processes of remodeling and healing of the bone [ 43 ]; usually, the achievement of good primary stability will be followed by correct secondary stability [ 44 ]. In this way, the dynamic functional response of the bone tissue is determined by the bone-to-implant contact percentage (BIC), which is constantly interested in remodeling processes under the functional loading [ 25 , 26 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ]. In order to assess the implant stability, we may use an index called the implant stability quotient (ISQ), a unit of measurement, which allows us to assess the degree of integration of the placed implants [ 49 ]; the clinical range of the ISQ is ranged between 55 and 80, and if the value is higher than 65, it is commonly accepted as a favorable situation for implant stability; on the contrary, values under 45 are considered as insufficient implant stability [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is the overall lower prevalence of comorbidities and extensive augmentative procedures, albeit these differences were not significant in this study. Nonetheless, it should be noted that in our previous work using a dataset of over 2400 implants in over 1100 patients, neither comorbidities nor surgical procedures could accurately predict early implant failure [26]. Third, the data suggest that datasets containing dental implant treatments during the pandemic are comparable to pre-pandemic datasets, allowing their use for training or validation of statistical models.…”
Section: Discussionmentioning
confidence: 74%